2012
DOI: 10.1063/1.4733327
|View full text |Cite
|
Sign up to set email alerts
|

Negative spin polarization at the Fermi level in Fe4N epitaxial films by spin-resolved photoelectron spectroscopy

Abstract: Related Articles Electronic band structure and optical phonons of BaSnO3 and Ba0.97La0.03SnO3 single crystals: Theory and experiment J. Appl. Phys. 112, 044108 (2012) Electronic, structural, and elastic properties of metal nitrides XN (X = Sc, Y): A first principle study AIP Advances 2, 032163 (2012) Effects of strain, d-band filling, and oxidation state on the surface electronic structure and reactivity of 3d perovskite surfaces

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…10 The spin-resolved photoemission spectra of Fe 4 N was measured near E F and its P D was confirmed to be negative. 11 This result is consistent with the inverse tunnel magnetoresistance ratio (À75%) reported in a Fe 4 N/MgO/CoFeB magnetic tunnel junction at room temperature (RT). 12 In contrast, it is difficult to experimentally obtain information about the sign of P r at RT.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…10 The spin-resolved photoemission spectra of Fe 4 N was measured near E F and its P D was confirmed to be negative. 11 This result is consistent with the inverse tunnel magnetoresistance ratio (À75%) reported in a Fe 4 N/MgO/CoFeB magnetic tunnel junction at room temperature (RT). 12 In contrast, it is difficult to experimentally obtain information about the sign of P r at RT.…”
Section: Introductionsupporting
confidence: 87%
“…At present, we cannot conclude whether this behavior is specific to Co 4 N. It may be necessary to use high-quality Co 4 N where the N atoms are located at the body center of each unit cell, to determine the exact sign of P r in Co 4 N from the sign of the AMR ratio. In sample A (Fe 4 N), P D < 0 was confirmed using both experiments and calculations, 10,11 indicating that P r should be negative according to Eq. (2).…”
Section: Experimental Methodsmentioning
confidence: 70%
“…12 Furthermore, spin-resolved photoemission spectroscopy study revealed the negative P D near E F for Fe 4 N films on STO(001) substrate. 13 Recently, a negative anisotropic magnetoresistance (AMR) effect was reported for Fe 4 N films. [14][15][16] To clarify the observed AMR, Kokado et al performed a model calculation and exhibited relationship between the sign of AMR signals and dominant s-d scattering process in ferromagnetic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have presented the AMR ratio of Fe 4 N, reporting ratios of À2.7% at 5 K, 13 À4.3% at 4.2 K, 14 and À6.2% at 4 K. 15 The negative sign of the P D has been anticipated by theory 16 and has been confirmed by experiments using spin-resolved photoelectron spectroscopy. 17 Another report on the inverse tunnel magnetoresistance effect in the Fe 4 N/MgO/CoFeB magnetic tunnel junction structure has also suggested that a negative P D is present in Fe 4 N. 19 For ferromagnetic thin films with perpendicular magnetic anisotropy (PMA), CIDM can be detected by various methods such as direct observation using the magnetooptical Kerr effect [20][21][22] and electrical measurement using the anomalous Hall effect. [23][24][25][26] For materials with in-plane magnetic anisotropy (IMA), on the other hand, the DW motion is Published by AIP Publishing.…”
Section: Introductionmentioning
confidence: 99%
“…12 The negative sign of the P r has been deduced from the negative anisotropic magnetoresistance (AMR) ratio, [13][14][15] and from the negative spin polarization of the density of states (D) at the Fermi level (E F ), P D . This spin polarization of the density of states is given by 16,17 and the relation that the AMR ratio is proportional to ÀP r P D is used. 18 The AMR ratio is given by…”
Section: Introductionmentioning
confidence: 99%